The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1373/clinchem.2013.211706
|View full text |Cite
|
Sign up to set email alerts
|

The Global Need to Define Normality: The 99th Percentile Value of Cardiac Troponin

Abstract: BACKGROUND:How to select a presumably normal population for the establishment of 99th percentile cutoffs for cardiac troponin assays has not been adequately addressed. Lack of attention to this question can result in misleading medical decision cutoffs.CONTENT: From our review of the peer-reviewed literature, including international recommendations, no uniform procedure is followed and no uniform guideline has been published by experts or regulatory agencies to guide researchers or manufacturers of cardiac tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 44 publications
1
98
0
3
Order By: Relevance
“…the criteria for considering the reference population "healthy") [17,[25][26][27][28][29], but also on the analytical performances of cTn methods, as well as on the mathematical algorithms used for calculating the 99th URL [10,14,15,17,18,25,26].…”
Section: Criteria For Calculating 99th Url Valuesmentioning
confidence: 99%
See 4 more Smart Citations
“…the criteria for considering the reference population "healthy") [17,[25][26][27][28][29], but also on the analytical performances of cTn methods, as well as on the mathematical algorithms used for calculating the 99th URL [10,14,15,17,18,25,26].…”
Section: Criteria For Calculating 99th Url Valuesmentioning
confidence: 99%
“…The approach for selecting a reference population for calculating the 99th percentile value for cTn assays has not yet been adequately defined [17]. The Third Universal Definition of Myocardial Infarction [3] reported that gender-dependent values might be recommended for highly sensitive troponin assays without specifying criteria for considering a population "healthy".…”
Section: Criteria For Selecting Reference Populationmentioning
confidence: 99%
See 3 more Smart Citations